2016
DOI: 10.1016/j.celrep.2016.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Insertional Mutagenesis Identifies a STAT3/Arid1b/β-catenin Pathway Driving Neurofibroma Initiation

Abstract: Summary To identify genes and signaling pathways that initiate Neurofibromatosis type 1 (Nf1) neurofibroma, we used unbiased insertional mutagenesis screening, mouse models, and molecular analyses. We mapped an Nf1-Stat3-Arid1b/β-catenin pathway which becomes active in the context of Nf1 loss. Genetic deletion of Stat3 in Schwann cells progenitors (SCPs) and Schwann cells (SCs) prevents neurofibroma formation, decreasing SCP self-renewal and β-catenin activity. β-catenin expression rescues effects of Stat3 los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 40 publications
4
55
0
Order By: Relevance
“…In macrophages, perturbation of the balance between phospho-STAT1 and phospho-STAT3 can redirect signaling. In neurofibroma macrophages, neither Stat1 nor the Stat1 target gene Il10 were differentially expressed; however, phospho-STAT3 is elevated58. Given that IFN-γ is elevated in neurofibroma yet IL10 is not, an IFN-γ-dependent STAT1-independent pathway may be relevant59.…”
Section: Discussionmentioning
confidence: 93%
“…In macrophages, perturbation of the balance between phospho-STAT1 and phospho-STAT3 can redirect signaling. In neurofibroma macrophages, neither Stat1 nor the Stat1 target gene Il10 were differentially expressed; however, phospho-STAT3 is elevated58. Given that IFN-γ is elevated in neurofibroma yet IL10 is not, an IFN-γ-dependent STAT1-independent pathway may be relevant59.…”
Section: Discussionmentioning
confidence: 93%
“…35 STAT3 has been shown to stimulate expression of b-catenin and repress GSK3b transcription. [38][39][40] Such mechanisms would thus be likely candidates to explain the observed synergistic activation of b-catenin in human CD49f 1 CB cells exposed to the 5 GFs studied here.…”
Section: Cd49fmentioning
confidence: 88%
“…For example, the neurofibroma model was used in an insertional mutagenesis screen to identify new effector pathways in NF1 -mutant tumors. Using this approach a Stat3-Arid1b/β-catenin pathway was found to be essential for neurofibroma formation (22), supporting the investigation of JAK/STAT and Wnt/β-catenin pathway inhibitors as potential therapeutic agents. Human genetic and mouse modeling studies also identified the epigenetic regulator, SUZ12, as an important tumor suppressor in MPNSTs (23).…”
Section: Successful Target Identification and Translationmentioning
confidence: 70%